Synthesis and Antimicrobial of 3-Phenyl-5,7-Dibromo-6-Methyl-4-Substituted Styrylcoumarin - Naik, S.M.; Naik, H.B. (Asian Journal of Chemistry, 2010)
Some new 4-styrylcoumarin derivatives have been prepared by condensation of 2´-phenylacetyloxy-5´-methyl-4´,6´-dibromochalcone with potassium hydroxide in presence of pyridine. The structure of the product has been characterised by element analysis and IR studies. The products have been screened for antibacterial activity against Staphylococcus aureus and Escherichia coli.